The Role Of Vacuole Membrane Protein-1 In Neural Calcium Homeostasis And Synaptic Plasticity - Wang, Mengmeng (2024)
Disruption of the intracellular calcium (Ca2+) dynamics is previously known to affect synaptic plasticity and cognitive function. To date, the effects of vacuole membrane protein 1 (VMP1) on neuronal intracellular calcium homeostasis, synaptic plasticity, and cognitive function remain unexplored. This study aimed to examine the effects of VMP1 on neuronal calcium regulation in vitro and in vivo, and its relationship with synaptic plasticity and cognitive function in vivo. VMP1 expression was knocked down in SH-SY5Y neuroblastoma cells and the effects on store-operated calcium entry (SOCE) and calcium channels were assessed using western blot. The in vivo gain-and-loss function of hippocampal VMP1 was achieved in C57/BL6 mice using the adeno-associated virus. The effects of VMP1 overexpression and downregulation on calcium channels, animal cognitive functions, long-term potentiation (LTP), neuron dendritic spine density, and synaptic-related proteins were evaluated. In vitro study showed that VMP1 knockdown reduced SOCE (p<0.0001), transient receptor potential canonical (TRPC1), and calcium release-activated calcium channel protein 1 (Orai1) in the SH-SY5Y neuroblastoma cells (n=4, P<0.01). Hippocampal VMP1 knockdown in mice led to decreased TRPC1 expression (n=4, P<0.01).